No. 44, The Mysterious Stranger: Mark Twain's critique of progressive era meritocracy. Issue 10 (3rd October 2022) - Collins, Michael J.
ABSTRACT: This paper argues that Mark Twain's under-studied final work No. 44, The Mysterious Stranger – left incomplete upon his death – is an exploration of the author's engagement with the question of the relationship between individual intelligence, brain science, and the emerging, Progressive Era discourse of 'merit'. I show how Twain's novel critiques 'merit' and the political structures of 'meritocracy' by presenting the reader with two characters who are in fact the same person (August and Forty-Four) to expose different facets of the meritocratic personality. These facets (a belief in innate ability and a commitment to impressibility and growth) might seem contradictory, but Twain's novel demonstrates how in a moment of advanced capitalism and industrialism that predicts our own both are deployed consciously by the meritocrat in the transfer of power from the collective to the bourgeois individual. With No. 44, The Mysterious Stranger, Twain refines his vision of American social values into a critique of the Enlightenment more broadly, abandoning his earlier reformist impulses to imagine more radical challenges to American power.